Child Well-Being: Where Is It in Our Data Systems?. Issue 4 (7th August 2016) - Jonson-Reid, Melissa; Drake, Brett
Abstract : Child well-being is a required goal for public child welfare. Despite this requirement, there continues to be no systematic inclusion of child well-being indicators in administrative data, particularly for children remaining in the home. This brief commentary provides a rationale and suggested steps for moving toward inclusion of well-being indicators as a part of standard electronic record-keeping. Suggested operationalized elements for inclusion in electronic records are offered as well as suggestions for linkage across systems to begin to capture elements of the outcome of well-being automatically. Limitations and barriers are discussed as well as present policy changes that may provide support for this endeavor.